Oxide dispersion strengthened iron-chromium-tungsten-based ferrite martensite alloy for lead-cooled fast reactor cladding and preparation method thereof

By adding ultrafine Y2O3 and Al to the lead-cooled fast stack encapsulation material, oxide dispersion strengthening and Al2O3 film formation are achieved, which solves the problem of insufficient performance of existing materials in high temperature, high neutron radiation and liquid Pb-Bi metal corrosion environments, and significantly improves the mechanical properties and radiation resistance of the materials.

CN119843180AActive Publication Date: 2025-04-18NUCLEAR POWER INSTITUTE OF CHINA
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510349164.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-18
Estimated Expiration
2045-03-24

Smart Images

  • Figure CN119843180A_ABST
    Figure CN119843180A_ABST
Patent Text Reader

Abstract

The invention provides an oxide dispersion strengthened iron-chromium-tungsten-based ferrite martensite alloy for a lead-cooled fast reactor cladding and a preparation method thereof, and belongs to the technical field of reactor structural materials, the alloy comprises the following components in percentage by mass: 9.0-12.0% of Cr, 0.15-0.25% of C, 1-2% of W, 0.5% of Mn, 0.2-0.5% of (Ta + V), 0.01-0.1% of (Zr + La), 1.0-5.0% of Al, 0.25-0.45% of Y2O3, and the balance of Fe, P, S, O and other impurity content lt; 0.003%, and the N content is lt; and 0.02% of the total weight. According to the oxide dispersion strengthened iron-chromium-tungsten-based ferrite martensite alloy for the lead-cooled fast reactor cladding and the preparation method of the oxide dispersion strengthened iron-chromium-tungsten-based ferrite martensite alloy, the alloy has excellent high-temperature mechanical property and liquid lead-bismuth metal corrosion resistance and has more uniform and refined grains.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of reactor structural materials, and in particular to an oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding and a preparation method thereof. Background Art

[0002] Nuclear energy is a clean and efficient energy source with the potential to replace fossil energy on a large scale. It occupies an important position in my country's current energy structure. In the process of large-scale sustainable utilization of nuclear energy, the following key issues are still faced: (1) greatly improve the utilization efficiency of nuclear fuel uranium, increase reactor burnup, and provide resource guarantee for large-scale sustainable development of nuclear power; (2) achieve safe disposal of nuclear waste, reduce the amount of nuclear waste, and realize green and environmentally friendly nuclear energy utilization. In order to solve the above key problems, the International Forum on the Fourth Generation of Nuclear Energy Systems (GIF) proposed six advanced reactor types, namely gas-cooled fast reactor, lead-cooled fast reactor, molten salt reactor, nano-cooled fast reactor, ultra-high gas-cooled reactor and supercritical water-cooled reactor, to systematically solve the problems of economy, safety, waste treatment and protection in the development of nuclear power. Among the above six pre-selected reactor types, lead-cooled fast reactor has attracted attention and importance due to its unique advantages in neutron economy, thermal hydraulic characteristics, chemical stability and safety. It is the focus of advanced nuclear energy system research and is expected to be the first to achieve industrial demonstration application in the fourth generation of nuclear energy systems.

[0003] The reliability of reactor cladding materials is one of the main bottlenecks restricting the sustainable use of advanced nuclear energy in the future, and determines the feasibility, safety and economy of nuclear energy systems. For the lead-cooled fast reactor of the fourth-generation advanced nuclear energy system, the irradiation and corrosion environment faced by its cladding materials will be more severe than that of the existing commercial fission reactors, and higher requirements are placed on the high-temperature strength, creep performance, radiation resistance and corrosion resistance of the cladding materials. For example, compared with the lower operating temperature (≤350℃) and neutron irradiation dose of most current commercial nuclear power plants, the service environment faced by the cladding components of lead-cooled fast reactors will be more demanding: (1) higher operating temperature (500℃-650℃); (2) harsh corrosion environment (liquid Pb-Bi metal solution corrosion); (3) high neutron irradiation dose: between 50-150dpa, up to 200dpa. For the cladding materials used in the current nuclear pressurized water reactors, such as zirconium alloys and austenitic stainless steel, they suffer from serious radiation swelling, radiation hardening and low Pb-Bi metal corrosion resistance under high temperature and high neutron irradiation. Therefore, they cannot fully meet the load requirements of fast neutron reactors such as lead-cooled fast reactors for cladding materials.

[0004] Ferrite / martensite (F / M) alloy is considered to be one of the most promising candidate cladding materials for lead-cooled fast reactors due to its superior comprehensive properties. However, traditional commercial and under-research F / M alloys are not specially designed for lead-cooled fast reactor cladding materials and still have considerable limitations in high-temperature strength, creep properties and resistance to lead-bismuth corrosion.

[0005] In addition, the quality of the material's corrosion resistance is one of the important factors that restrict its application in lead-cooled fast reactor cladding materials. In the fourth-generation advanced nuclear energy system, liquid metal lead or lead-bismuth eutectic (LBE) is used as a coolant. Liquid metal corrosion will cause changes in the material's microstructure, composition and surface morphology, thereby affecting the material's mechanical and physical properties. Therefore, when designing cladding materials for lead-based reactors, special consideration needs to be given to the cladding material's resistance to liquid LBE corrosion.

[0006] Therefore, there is an urgent need for an oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding with excellent high-temperature mechanical properties and excellent resistance to liquid lead-bismuth metal corrosion. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide an oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding having excellent high temperature mechanical properties and excellent resistance to liquid lead-bismuth metal corrosion and a preparation method thereof.

[0008] In order to solve the above technical problems, the present invention provides an oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding, which comprises, by mass percentage, 9.0-12.0% Cr, 0.15-0.25% C, 1-2% W, 0.5% Mn, 0.2-0.5% (Ta+V), 0.01-0.1% (Zr+La), 1.0-5.0% Al, 0.25-0.45% Y2O3, and the rest is Fe, the impurity content of P, S, O etc. is <0.003%, and the N content is <0.02%.

[0009] The present invention also provides a method for preparing an oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding, comprising the following steps: In terms of mass percentage, 9.0-12.0% Cr, 0.15-0.25% C, 1-2% W, 0.5% Mn, 0.2-0.5% (Ta+V), 0.01-0.1% (Zr+La), 0.1-5.0% Al, and the rest is Fe, with impurity contents such as P, S, and O being less than 0.003% and N content being less than 0.02% to obtain a pre-alloyed powder; Adding 0.25-0.45% by mass of Y2O3 with a particle size of ≤20nm into the pre-alloyed powder and ball-milling under vacuum and protective atmosphere to obtain alloyed powder; Sieving the alloyed powder and sintering the sieved powder under a protective atmosphere to obtain a sintered alloy nugget; The sintered alloy block is clad and hot rolled and then subjected to final heat treatment to obtain an oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding.

[0010] Furthermore, the pre-alloyed powder and Y2O3 are ball-milled in a vacuum glove box, with a ball-to-material ratio of 5:1-15:1, a filling coefficient of 0.3-0.5, a ball-milling speed of 300-400 rpm, and alloyed powder is obtained after ball-milling for 40-60 h.

[0011] Furthermore, the alloyed powder is sieved by sequentially sieving the alloyed powder using 200-mesh and 500-mesh sieves to obtain sieved powder.

[0012] Furthermore, the sintering molding of the sieved powder is to put the sieved powder into a graphite mold with a diameter of 10-30 mm in a vacuum glove box, and perform spark plasma sintering molding under a protective atmosphere.

[0013] Furthermore, during sintering of the sieved powder, the powder is heated to 1000-1100° C. at a rate of 50-150° C. / min, the sintering pressure is 40-60 MPa, and the sintering time is 5-10 min.

[0014] Furthermore, the protective atmosphere is high-purity argon gas with a purity of more than 99.99%.

[0015] Furthermore, the hot rolling temperature of the sintered alloy block during the sheath hot rolling is 1000-1100° C., the holding time is 20-40 min, the reduction is about 75-85%, the holding interval between each pass is 5-10 min, and the sheath is removed after hot rolling.

[0016] Furthermore, the final heat treatment includes normalizing treatment for austenitizing and tempering treatment for stress relief and carbide precipitation.

[0017] Furthermore, the normalizing treatment temperature is 950-1150° C., the holding time is 50-80 minutes, and then quenching and water cooling; the tempering treatment temperature is 700-750° C., the holding time is 80-100 minutes, and then air cooling.

[0018] The present invention provides an oxide dispersion strengthened iron-chromium-tungsten based ferrite-martensitic alloy for lead-cooled fast reactor cladding. The alloy is based on an oxide dispersion strengthened iron-chromium-tungsten based ferrite / martensitic iron alloy, wherein 0.25-0.45% by mass of ultrafine Y2O3 (≤20nm) particles with extremely high thermal stability and chemical stability are added and dispersed in the alloy matrix. This can not only hinder dislocation movement and improve the high-temperature strength and high-temperature creep performance of the material, but also the dispersed Y2O3 nanoparticles can well annihilate the defects caused by radiation and enhance the radiation resistance of the material.

[0019] In addition, the present invention provides an oxide dispersion strengthened iron-chromium-tungsten based ferrite-martensitic alloy for lead-cooled fast reactor cladding. The alloy is based on the oxide dispersion strengthened iron-chromium-tungsten based ferrite / martensitic alloy, and 0.1%-5.0% Al is added to the alloy, which can not only improve the toughness and machinability of the alloy, but also form a dense Al2O3 film on the surface of the alloy, thereby effectively enhancing the alloy's resistance to dissolution corrosion by LBE coolant.

[0020] Therefore, the invention provides a method for preparing an oxide dispersion-strengthened iron-chromium-tungsten-based ferrite martensitic alloy for lead-cooled fast reactor cladding. The prepared oxide dispersion-strengthened iron-chromium-tungsten-based ferrite martensitic alloy for lead-cooled fast reactor cladding not only has good resistance to liquid lead-bismuth metal corrosion, but also has more uniform and refined grains. At the same time, the mechanical properties at a high temperature of 600°C are also significantly improved, and the fracture strength at a high temperature of 600°C can reach more than 437Mpa. It is used as a core structural material such as a fuel element cladding and a grid in a fourth-generation reactor, especially in a lead-cooled fast reactor, and exhibits high mechanical properties and resistance to lead-bismuth corrosion. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A flow chart of a method for preparing an oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding provided by an embodiment of the present invention; Figure 2 Mechanical property test curve at 600°C of oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding prepared by the alloy preparation method provided in Examples 1-5 of the present invention; Figure 3 This is a grain size distribution diagram of the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding prepared by the alloy preparation method provided in Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0022] An embodiment of the present invention provides an oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for a lead-cooled fast reactor cladding, which comprises, by mass percentage, 9.0-12.0% Cr, 0.15-0.25% C, 1-2% W, 0.5% Mn, 0.2-0.5% (Ta+V), 0.01-0.1% (Zr+La), 1.0-5.0% Al, 0.25-0.45% Y2O3, and the rest is Fe, and the impurity content of P, S, O, etc. is <0.003%, and the N content is <0.02%.

[0023] The present invention provides an oxide dispersion strengthened iron-chromium-tungsten based ferrite-martensitic alloy for lead-cooled fast reactor cladding. The alloy is based on an oxide dispersion strengthened iron-chromium-tungsten based ferrite / martensitic iron alloy, wherein 0.25-0.45% by mass of ultrafine Y2O3 (≤20nm) particles with extremely high thermal stability and chemical stability are added and dispersed in the alloy matrix. This can not only hinder dislocation movement and improve the high-temperature strength and high-temperature creep performance of the material, but also the dispersed Y2O3 nanoparticles can well annihilate the defects caused by radiation and enhance the radiation resistance of the material.

[0024] In addition, the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding provided by the present invention further adds 0.1%-5.0% Al to the alloy, which can not only improve the toughness and machinability of the alloy, but also form a dense Al2O3 film on the surface of the alloy, thereby effectively enhancing the alloy's resistance to dissolution corrosion by LBE coolant.

[0025] See also Figure 1 The present invention also provides a method for preparing an oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding, comprising the following steps: Step 1) In terms of mass percentage, 9.0-12.0% Cr, 0.15-0.25% C, 1-2% W, 0.5% Mn, 0.2-0.5% (Ta+V), 0.01-0.1% (Zr+La), 0.1-5.0% Al, and the rest is Fe, with impurity contents such as P, S, and O <0.003% and N content <0.02% mixed to obtain a pre-alloyed powder.

[0026] Step 2) Add 0.25-0.45% by mass of Y2O3 to the obtained pre-alloyed powder and ball-mill under vacuum and protective atmosphere to obtain alloyed powder, wherein Y2O3 serves as an oxide dispersion strengthening phase of the alloy.

[0027] Specifically, the pre-alloyed powder and Y2O3 are placed in a ball mill in a vacuum glove box. Before ball milling, argon gas with a purity of 99.99% is passed for protection to prevent the metal in the alloy powder from being oxidized by oxygen in the air during the subsequent ball milling process. For the best ball milling effect, the ball-to-material ratio is controlled to 5:1-15:1, the filling coefficient is controlled to 0.3-0.5, and the ball milling speed is controlled to 300-400 rpm. After ball milling for 40-60 hours, the alloyed powder is obtained.

[0028] Step 3) The alloyed powder obtained after ball milling is screened to obtain screened powder. In order to achieve the best screening effect, when screening the alloyed powder, 200 mesh and 500 mesh sieves are used in sequence to screen the alloyed powder to obtain screened powder.

[0029] Step 4) Sintering the sieved powder obtained by sieving under a protective atmosphere to obtain a sintered alloy block.

[0030] Specifically, when the sieved powder is sintered, the sieved powder is placed in a graphite mold with a diameter of 10-30 mm in a vacuum glove box, and spark plasma (SPS) sintering is performed under a protective atmosphere.

[0031] When the screened powder is sintered, it is heated to 1000-1100°C at a heating rate of 50-150°C / min, and the sintering pressure is controlled to be 40-60MPa, and the sintering time is 5-10 min to obtain a sintered alloy block.

[0032] Among them, the protective atmosphere is high-purity argon gas with a purity of more than 99.99%.

[0033] The present invention provides a method for preparing an oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding. The alloy powder is sintered and formed by spark plasma sintering, which can not only shorten the preparation time and improve the preparation efficiency, but also the prepared oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy has fine grains and more uniform and refined grains.

[0034] Step 5) hot rolling the sintered alloy block obtained by sintering. In order to keep the temperature during hot rolling and improve the deformation uniformity of the surface of the rolled material, the sintered alloy block is hot rolled by using a jacket.

[0035] The hot rolling temperature of the sintered alloy block during sheath hot rolling is 1000-1100°C, the holding time is 20-40 min, the reduction is about 75-85%, the holding interval between each pass is 5-10 min, and the sheath is removed after hot rolling.

[0036] Step 6) performing a final heat treatment on the alloy after hot rolling to obtain an oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding.

[0037] The final heat treatment of the alloy material includes a normalizing treatment for austenitizing the alloy material and a tempering treatment for stress relief and carbide precipitation of the alloy material.

[0038] The normalizing treatment temperature is 950-1150°C, the holding time is 50-80 minutes, and then quenching and water cooling are performed.

[0039] The tempering treatment temperature is 700-750°C, kept at this temperature for 80-100 minutes, and then air-cooled.

[0040] The invention provides a method for preparing an oxide dispersion strengthened iron-chromium-tungsten-based ferrite martensitic alloy for lead-cooled fast reactor cladding, which is based on the oxide dispersion strengthened iron-chromium-tungsten-based ferrite martensitic alloy, and adds 0.25-0.45% Y2O3 and 0.1%-5.0% Al in the alloy mass percentage, and finally obtains the oxide dispersion strengthened iron-chromium-tungsten-based ferrite martensitic alloy for lead-cooled fast reactor cladding through ball milling, spark plasma sintering, jacket hot rolling and final heat treatment. The alloy not only has good resistance to liquid lead-bismuth metal corrosion, but also has more uniform and refined grains, and the mechanical properties at a high temperature of 600°C are also significantly improved, and the fracture strength at a high temperature of 600°C can reach more than 437Mpa. The alloy is applied to the core structural materials such as the fuel element cladding and grid in the fourth generation reactor, especially in the lead-cooled fast reactor, and can show higher mechanical properties and resistance to lead-bismuth corrosion.

[0041] The oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding provided by the present invention and its preparation method are specifically described below through examples.

[0042] Example 1 (1) 9.0-12.0% Cr, 0.15-0.25% C, 1-2% W, 0.5% Mn, 0.2-0.5% (Ta+V), 0.01-0.1% (Zr+La) alloy powders are mixed in proportion, and the rest is Fe. All the above are mass percentages.

[0043] (2) The pre-alloyed powder and 0.35% Y2O3 (i.e., oxide dispersion strengthening phase) were placed in a ball mill in a vacuum glove box. Pure argon (purity of 99.99%) was passed through the mill for protection before ball milling. The ball-to-material ratio was 10:1 and the filling factor was 0.4. The ball milling speed was 350 rpm. After 50 h of ball milling, alloyed powder was obtained. (3) Sieve with 200-mesh and 500-mesh sieves, and place the sieved powder into a graphite mold with a diameter of 20 mm in a vacuum glove box. Sinter the powder by spark plasma (SPS) in a high-purity argon environment, and heat it to 1050 °C at a rate of 100 °C / min, with a sintering pressure of 50 MPa and a sintering time of 5 min. (4) After sintering, the material is hot rolled. The hot rolling is jacket hot rolling. The hot rolling temperature is 1100°C, the holding time is 30 min, the reduction is about 80%, and the holding interval between each pass is 5 min. The jacket is removed after hot rolling. (5) After rolling, austenitizing treatment and normalizing are carried out: 1100℃ for 60 minutes, quenching, and water cooling; (6) The material is then subjected to stress relief and carbide precipitation tempering: 750°C for 90 minutes, air-cooled, and the resulting lead-cooled fast reactor cladding is an oxide-dispersion-strengthened iron-chromium-tungsten based ferrite martensitic alloy.

[0044] Ten test points on the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding prepared in the embodiment of the present invention were respectively tested for micro-Vickers hardness in the final heat treatment state. The test results are shown in Table 1.

[0045] Table 1

[0046] The tensile strength mechanical property test of the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding prepared in the embodiment of the present invention was carried out at 600°C. The test results are shown in Table 2.

[0047] Table 2

[0048] The tensile mechanical properties of the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding prepared in the embodiment of the present invention were tested at 600°C. The tensile test curve obtained is as follows: Figure 2 As shown in 0Al.

[0049] Figure 3 (a) is a grain size distribution diagram of the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding obtained by EBSD in an embodiment of the present invention.

[0050] Example 2 (1) 9.0-12.0% Cr, 0.15-0.25% C, 1-2% W, 0.5% Mn, 0.2-0.5% (Ta+V), 0.01-0.1% (Zr+La), 1.0% Al alloy powders are mixed in proportion, and the rest is Fe, all of which are in mass percentage; (2) The pre-alloyed powder and 0.35% Y2O3 (i.e., oxide dispersion strengthening phase) were placed in a ball mill in a vacuum glove box. Pure argon (purity of 99.99%) was passed through the mill for protection before ball milling. The ball-to-material ratio was 10:1 and the filling factor was 0.4. The ball milling speed was 350 rpm. After 50 h of ball milling, alloyed powder was obtained. (3) Sieve with 200-mesh and 500-mesh sieves, and place the sieved powder into a graphite mold with a diameter of 20 mm in a vacuum glove box. Sinter the powder by spark plasma (SPS) in a high-purity argon environment, and heat it to 1050 °C at a rate of 100 °C / min, with a sintering pressure of 50 MPa and a sintering time of 5 min. (4) After sintering, the material is hot rolled. The hot rolling is jacket hot rolling. The hot rolling temperature is 1100°C, the holding time is 30 min, the reduction is about 80%, and the holding interval between each pass is 5 min. The jacket is removed after hot rolling. (5) After rolling, austenitizing treatment and normalizing are carried out: 1100℃ for 60 minutes, quenching, and water cooling; (6) The material is then subjected to stress relief and carbide precipitation tempering: 750°C for 90 minutes, air-cooled, and the resulting lead-cooled fast reactor cladding is an oxide-dispersion-strengthened iron-chromium-tungsten based ferrite martensitic alloy.

[0051] Ten test points on the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding prepared in the embodiment of the present invention were respectively tested for micro-Vickers hardness in the final heat treatment state. The test results are shown in Table 1.

[0052] The tensile strength mechanical property test of the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding prepared in the embodiment of the present invention was carried out at 600°C. The test results are shown in Table 2.

[0053] The tensile mechanical properties of the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding prepared in the embodiment of the present invention were tested at 600°C. The tensile test curve obtained is as follows: Figure 2 As shown in 1Al.

[0054] Figure 3 (b) is a grain size distribution diagram of the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding obtained by EBSD in an embodiment of the present invention.

[0055] Compared with Example 1, when the same amount of Y2O3 is added to the alloy, the high temperature tensile strength of the alloy material at 600°C is 1.0% Al added to the alloy in the embodiment of the present invention. R m =483.95MPa, compared with the alloy material without Al in Example 1 R m =430.74Mpa, the tensile strength of the alloy prepared in the embodiment of the present invention is increased by 12.35%. Example 3 (1) 9.0-12.0% Cr, 0.15-0.25% C, 1-2% W, 0.5% Mn, 0.2-0.5% (Ta+V), 0.01-0.1% (Zr+La), 3.0% Al alloy powders are mixed in proportion, and the rest is Fe, all of which are mass percentages; (2) The pre-alloyed powder and 0.35% Y2O3 (i.e., oxide dispersion strengthening phase) were placed in a ball mill in a vacuum glove box. Pure argon (purity of 99.99%) was passed through the mill for protection before ball milling. The ball-to-material ratio was 10:1 and the filling factor was 0.4. The ball milling speed was 350 rpm. After 50 h of ball milling, alloyed powder was obtained. (3) Sieve with 200-mesh and 500-mesh sieves, and place the sieved powder into a graphite mold with a diameter of 20 mm in a vacuum glove box. Sinter the powder by spark plasma (SPS) in a high-purity argon environment, and heat it to 1050 °C at a rate of 100 °C / min, with a sintering pressure of 50 MPa and a sintering time of 5 min. (4) After sintering, the material is hot rolled. The hot rolling is jacket hot rolling. The hot rolling temperature is 1100°C, the holding time is 30 min, the reduction is about 80%, and the holding interval between each pass is 5 min. The jacket is removed after hot rolling. (5) After rolling, austenitizing treatment and normalizing are carried out: 1100℃ for 60 minutes, quenching, and water cooling; (6) The material is then subjected to stress relief and carbide precipitation tempering: 750°C for 90 minutes, air-cooled, and the resulting lead-cooled fast reactor cladding is an oxide-dispersion-strengthened iron-chromium-tungsten based ferrite martensitic alloy.

[0056] Ten test points on the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding prepared in the embodiment of the present invention were respectively tested for micro-Vickers hardness in the final heat treatment state. The test results are shown in Table 1.

[0057] The tensile strength mechanical property test of the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding prepared in the embodiment of the present invention was carried out at 600°C. The test results are shown in Table 2.

[0058] The tensile mechanical properties of the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding prepared in the embodiment of the present invention were tested at 600°C. The tensile test curve obtained is as follows: Figure 2 As shown in 3Al.

[0059] Figure 3 (c) is a grain size distribution diagram of the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding obtained by EBSD in an embodiment of the present invention.

[0060] Compared with Example 1, when the same amount of Y2O3 is added to the alloy, the high temperature tensile strength of the alloy material at 600°C is 1.0% Al added to the alloy in the embodiment of the present invention. R m =462.05MPa, compared with the alloy material without Al in Example 1 R m =430.74Mpa, the tensile strength of the alloy prepared in the embodiment of the present invention is increased by 7.27%. Example 4 (1) 9.0-12.0% Cr, 0.15-0.25% C, 1-2% W, 0.5% Mn, 0.2-0.5% (Ta+V), 0.01-0.1% (Zr+La), 5.0% Al alloy powders are mixed in proportion, and the rest is Fe, all of which are mass percentages; (2) The pre-alloyed powder and 0.35% Y2O3 (i.e., oxide dispersion strengthening phase) were placed in a ball mill in a vacuum glove box. Pure argon (purity of 99.99%) was passed through the mill for protection before ball milling. The ball-to-material ratio was 10:1 and the filling factor was 0.4. The ball milling speed was 350 rpm. After 50 h of ball milling, alloyed powder was obtained. (3) Sieve with 200-mesh and 500-mesh sieves, and place the sieved powder into a graphite mold with a diameter of 20 mm in a vacuum glove box. Sinter the powder by spark plasma (SPS) in a high-purity argon environment, and heat it to 1050 °C at a rate of 100 °C / min, with a sintering pressure of 50 MPa and a sintering time of 5 min. (4) After sintering, the material is hot rolled. The hot rolling is jacket hot rolling. The hot rolling temperature is 1100°C, the holding time is 30 min, the reduction is about 80%, and the holding interval between each pass is 5 min. The jacket is removed after hot rolling. (5) After rolling, austenitizing treatment and normalizing are carried out: 1100℃ for 60 minutes, quenching, and water cooling; (6) The material is then subjected to stress relief and carbide precipitation tempering: 750°C for 90 minutes, air-cooled, and the resulting lead-cooled fast reactor cladding is an oxide-dispersion-strengthened iron-chromium-tungsten based ferrite martensitic alloy.

[0061] Ten test points on the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding prepared in the embodiment of the present invention were respectively tested for micro-Vickers hardness in the final heat treatment state. The test results are shown in Table 1.

[0062] The tensile strength mechanical property test of the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding prepared in the embodiment of the present invention was carried out at 600°C. The test results are shown in Table 2.

[0063] The tensile mechanical properties of the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding prepared in the embodiment of the present invention were tested at 600°C. The tensile test curve obtained is as follows: Figure 2 As shown in 5Al.

[0064] Figure 3 (d) is a grain size distribution diagram of the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding obtained by EBSD in an embodiment of the present invention.

[0065] Compared with Example 1, when the same amount of Y2O3 is added to the alloy, the high temperature tensile strength of the alloy material at 600°C is 1.0% Al added to the alloy in the embodiment of the present invention. R m =437.49MPa, compared with the alloy material without Al in Example 1 R m =430.74Mpa, the tensile strength of the alloy prepared in the embodiment of the present invention is higher than the tensile strength of the alloy in Example 1. And, from Figure 3It can be seen that in the case of adding 0.35% Y2O3 to the alloy in Examples 1-4 of the present invention, the average grain size of the ferrite martensitic alloy obtained in Example 1 of the present invention without adding Al to the alloy is 1.04 microns, the average grain size of the ferrite martensitic alloy obtained in Example 2 of the present invention with 1% Al added to the alloy is 0.62 microns, the average grain size of the ferrite martensitic alloy obtained in Example 3 of the present invention with 3% Al added to the alloy is 9.16 microns, and the average grain size of the ferrite martensitic alloy obtained in Example 4 of the present invention with 5% Al added to the alloy is 8.96 microns. In addition, the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding obtained by adding 1% Al and 0.35% Y2O3 to the alloy has the smallest grain size.

[0066] Comparative Example (1) 9.0-12.0% Cr, 0.15-0.25% C, 1-2% W, 0.5% Mn, 0.2-0.5% (Ta+V), 0.01-0.1% (Zr+La) alloy powders are mixed in proportion, and the rest is Fe, all of which are mass percentages; (2) The pre-alloyed powder was placed in a ball mill in a vacuum glove box. Pure argon (purity of 99.99%) was passed through the mill for protection before ball milling. The ball-to-material ratio was 10:1 and the filling factor was 0.4. The ball milling speed was 350 rpm. After ball milling for 50 h, the alloyed powder was obtained. (3) Sieve with 200-mesh and 500-mesh sieves, and place the sieved powder into a graphite mold with a diameter of 20 mm in a vacuum glove box. Sinter the powder by spark plasma (SPS) in a high-purity argon environment, and heat it to 1050 °C at a rate of 100 °C / min, with a sintering pressure of 50 MPa and a sintering time of 5 min. (4) After sintering, the material is hot rolled. The hot rolling is jacket hot rolling. The hot rolling temperature is 1100°C, the holding time is 30 min, the reduction is about 80%, and the holding interval between each pass is 5 min. The jacket is removed after hot rolling. (5) After rolling, austenitizing treatment and normalizing are carried out: 1100℃ for 60 minutes, quenching, and water cooling; (6) The material is then subjected to stress relief and carbide precipitation tempering: 750°C for 90 minutes, air-cooled, and the resulting lead-cooled fast reactor cladding is an oxide-dispersion-strengthened iron-chromium-tungsten based ferrite martensitic alloy.

[0067] Ten test points were taken on the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding prepared in the comparative example of the present invention to perform micro Vickers hardness tests in the final heat treatment state. The test results are shown in Table 1.

[0068] It can be seen from Table 1 that compared with the ferrite martensitic alloy in the control example without adding Al and Y2O3, the hardness of the ferrite martensitic alloy in Examples 1-4 of the present invention is significantly improved after adding 0.35% Y2O3 to the alloy, and the hardness of the ferrite martensitic alloy obtained by adding 1% Al and 0.35% Y2O3 to the alloy in Example 2 of the present invention reaches the maximum value.

[0069] The tensile strength mechanical property test of the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding prepared in the comparative example of the present invention was carried out at 600° C. The test results are shown in Table 2.

[0070] It can be seen from Table 2 that compared with the ferrite martensitic alloy obtained in the control example without adding Al and Y2O3, the tensile strength of the ferrite martensitic alloys in Examples 1-4 of the present invention is significantly improved after adding 0.35% Y2O3 to the alloy, and the tensile strength of the ferrite martensitic alloy obtained by adding 1% Al and 0.35% Y2O3 in Example 2 of the present invention is significantly improved and reaches a maximum value.

[0071] The tensile mechanical properties of the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding prepared in the comparative example of the present invention were tested at 600°C. The tensile test curve obtained is as follows: Figure 2 As shown in the comparison sample.

[0072] And, from Figure 2 It can also be seen that compared with the ferrite martensitic alloy obtained in the control example without adding Al and Y2O3, the tensile strength of the ferrite martensitic alloy in Examples 1-4 of the present invention is significantly improved after adding 0.35% Y2O3 to the alloy, and the tensile strength of the ferrite martensitic alloy obtained by adding 1% Al and 0.35% Y2O3 in Example 2 of the present invention is significantly improved and reaches a maximum value.

[0073] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. An oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding, characterized in that: In terms of mass percentage, it includes 9.0-12.0% Cr, 0.15-0.25% C, 1-2% W, 0.5% Mn, 0.2-0.5% (Ta+V), 0.01-0.1% (Zr+La), 1.0-5.0% Al, 0.25-0.45% Y2O3, and the rest is Fe. The impurity content of P, S, and O is <0.003%, and the N content is <0.02%.

2. A method for preparing an oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding, characterized in that: The steps include: In terms of mass percentage, 9.0-12.0% Cr, 0.15-0.25% C, 1-2% W, 0.5% Mn, 0.2-0.5% (Ta+V), 0.01-0.1% (Zr+La), 0.1-5.0% Al, the rest is Fe, the impurity content of P, S, O is less than 0.003%, and the content of N is less than 0.02% to obtain a pre-alloyed powder; Adding 0.25-0.45% by mass of Y2O3 with a particle size of ≤20nm into the pre-alloyed powder and ball-milling under vacuum and protective atmosphere to obtain alloyed powder; Sieving the alloyed powder and sintering the sieved powder under a protective atmosphere to obtain a sintered alloy nugget; The sintered alloy block is clad and hot rolled and then subjected to final heat treatment to obtain an oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding.

3. The method for preparing the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding according to claim 2, characterized in that: The pre-alloyed powder and Y2O3 are ball-milled in a vacuum glove box, with a ball-to-material ratio of 5:1-15:1, a filling coefficient of 0.3-0.5, a ball-milling speed of 300-400 rpm, and alloyed powder is obtained after ball-milling for 40-60 hours.

4. The method for preparing the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding according to claim 2, characterized in that: The alloyed powder is sieved by sequentially sieving the alloyed powder using 200-mesh and 500-mesh sieves to obtain sieved powder.

5. The method for preparing the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding according to claim 4, characterized in that: The sintering molding of the sieved powder is to put the sieved powder into a graphite mold with a diameter of 10-30 mm in a vacuum glove box, and perform spark plasma sintering molding under a protective atmosphere.

6. The method for preparing the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding according to claim 2, characterized in that: When the sieved powder is sintered, it is heated to 1000-1100° C. at a rate of 50-150° C. / min, the sintering pressure is 40-60 MPa, and the sintering time is 5-10 min.

7. The method for preparing the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding according to claim 2, characterized in that: The protective atmosphere is high-purity argon gas with a purity of more than 99.99%.

8. The method for preparing the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding according to claim 2, characterized in that: The hot rolling temperature of the sintered alloy block during the sheath hot rolling is 1000-1100° C., the holding time is 20-40 min, the reduction is 75-85%, the holding interval between each pass is 5-10 min, and the sheath is removed after hot rolling.

9. The method for preparing the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding according to claim 2, characterized in that: The final heat treatment includes a normalizing treatment for austenitizing and a tempering treatment for stress relief and carbide precipitation.

10. The method for preparing the oxide dispersion strengthened iron-chromium-tungsten based ferrite martensitic alloy for lead-cooled fast reactor cladding according to claim 9, characterized in that: The normalizing treatment temperature is 950-1150° C., the heat preservation time is 50-80 minutes, and then quenching and water cooling are performed; the tempering treatment temperature is 700-750° C., the heat preservation time is 80-100 minutes, and then air cooling is performed.

Citation Information

Patent Citations

  • Oxide-dispersion-strengthening ferrite / martensitic steel and preparing method

    CN105039857A

  • Method for refining residual ferrite in oxide dispersion strengthened (ODS) martensite steel

    CN107058852A

  • Method for preparing oxide dispersion strengthened steel by adopting ultralow-temperature mechanical alloying technology

    CN107699775A

  • Application of ferrite-based ODS steel under supercritical water service condition

    CN110885954A

  • Anti-corrosion anti-irradiation high-strength super ODS steel and preparing method

    CN111057958A